2018
DOI: 10.1038/s41366-018-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Infant temperament and parent use of food to soothe predict change in weight-for-length across infancy: early risk factors for childhood obesity

Abstract: ObjectivesGreater weight gain in infancy is a risk factor for childhood obesity. The present study examined the interaction between infant temperament and parent use of food to soothe infant distress (FTS) as predictors of weight gain across the first 2 years of life.Subjects/Methods160 mother-infant dyads were recruited into a longitudinal study. Infant temperament was assessed by parents through a questionnaire (surgency, negativity) and by observer ratings (surgency, irritability) during a laboratory visit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 44 publications
2
45
1
Order By: Relevance
“…More specifically, extraversion has been positively associated with overweight, possibly mediated by enjoyment of food and overeating habits in response to external cues [27,28]. Importantly, a recent study suggested that surgent infants only predicted increased weight gain during infancy when parents used food to soothe infant distress [29].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…More specifically, extraversion has been positively associated with overweight, possibly mediated by enjoyment of food and overeating habits in response to external cues [27,28]. Importantly, a recent study suggested that surgent infants only predicted increased weight gain during infancy when parents used food to soothe infant distress [29].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…We hypothesize that mothers receiving the RP intervention will report lower child emotional overeating than the control group, and that this effect is mediated by mothers' use of food to soothe. Based on previous data that infant negativity impacts mothers' use of food to soothe, 21 an exploratory aim of this study was to examine whether this process varied by infant negative affect.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral determinants associated with large infant size and rapid growth include short durations of exclusive breastfeeding (EBF) or any breastfeeding (BF) [7], introduction of complementary foods (CF) before 4 months [8,9], short sleep duration [10,11], early emergence of potentially obesogenic diets [12][13][14][15], and high levels of screentime [16][17][18]. Importantly, there is growing evidence on modifiable factors associated with early life feeding and care behaviors, including infant feeding attitudes, intentions, self-efficacy, and social support [19][20][21][22][23][24], as well as parental feeding styles [25,26] and appropriate interpretation of infant fussiness [27][28][29].…”
Section: Introductionmentioning
confidence: 99%